Exploring Intimacy with Artificial Intelligence : Validation of Robot Intimacy Receptivity Scale (RIRS) - Balazadeh, Kitty; Kajonius, Petri (International Journal of Social Robotics, 2025)
Public and scientific interest in human-robot interactions is growing rapidly. As artificial intelligence (AI) becomes an integral part of human experience, there is an urgent need to understand people’s receptivity to it, especially in emotionally intimate or private spheres. Intimate receptivity goes beyond general technology attitudes, carrying potential implications for companionship, mental health, ethical considerations, and the design of socially responsive robots. To explore this emerging construct, the goal of this two-study paper was to develop a new psychometric scale, the Robot Intimacy Receptivity Scale (RIRS), to assess people’s intimate receptivity to embodied AI and social robots. The factor structure, reliability, and validity of the RIRS were investigated in two independent samples (N = 572). In Study I (N = 261), exploratory factor analysis revealed excellent internal consistency (α = 0.94) and three distinct yet highly correlated content domains: communication, social distance, and personal intimacy. In Study II (N = 311), confirmatory factor analysis established one higher-order general factor and overall good model fit. Additionally, the summarized one-factor RIRS demonstrated convergence and divergence with existing human-robot interaction scales. These findings underscore the RIRS’s potential as a valuable tool for future research on the evolving dynamics of human-robot relationships in an era of rapidly advancing AI technologies and shifting social norms. The discussion section addresses the framework and the strengths and weaknesses of the present study. Further validation of the RIRS is recommended for future research.
Publisher Copyright: © The Author(s) 2025.
Keywords: Artificial intelligence; Companion AI; Human-robot interaction; RIRS; Robot intimacy; Robot intimacy receptivity scale; Scale validation; Social AI; Social robots